COVID-19 myth-busting: an experimental study - Aimée Challenger; Petroc Sumner; Lewis Bott (BMC, 2022)
Abstract Background COVID-19 misinformation is a danger to public health. A range of formats are used by health campaigns to correct beliefs but data on their effectiveness is limited. We aimed to identify A) whether three commonly used myth-busting formats are effective for correcting COVID-19 myths, immediately and after a delay, and B) which is the most effective. Methods We tested whether three common correction formats could reduce beliefs in COVID-19 myths: (i) question-answer, ii) fact-only, (ii) fact-myth. n = 2215 participants (n = 1291 after attrition), UK representative of age and gender, were randomly assigned to one of the three formats. n = 11 myths were acquired from fact-checker websites and piloted to ensure believability. Participants rated myth belief at baseline, were shown correction images (the intervention), and then rated myth beliefs immediately post-intervention and after a delay of at least 6 days. A partial replication, n = 2084 UK representative, was also completed with immediate myth rating only. Analysis used mixed models with participants and myths as random effects. Results Myth agreement ratings were significantly lower than baseline for all correction formats, both immediately and after the delay; all β's > 0.30, p's < .001. Thus, all formats were effective at lowering beliefs in COVID-19 misinformation. Correction formats only differed where baseline myth agreement was high, with question-answer and fact-myth more effective than fact-only immediately; β = 0.040, p = .022 (replication set: β = 0.053, p = .0075) and β = − 0.051, p = .0059 (replication set: β = − 0.061, p < .001), respectively. After the delay however, question-answer was more effective than fact-myth, β = 0.040, p =. 031. Conclusion Our results imply that COVID-19 myths can be effectively corrected using materials and formats typical of health campaigns. Campaign designers can use our results to choose between correction formats. When myth belief was high, question-answer format was more effective than a fact-only format immediately post-intervention, and after delay, more effective than fact-myth format.